2019
DOI: 10.29173/mocs84
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Tool for Enhancing the Economic Impact of Construction using Offsite Systems

Abstract: The construction industry is facing productivity stagnation across the globe, and several hypotheses to explain this phenomenon exist, most often associated with low use of digitisation, skills shortages and unpredictable market trends. Yet the economic context is more multi-faceted and the different economic drivers are closely interconnected, however research typically addresses each in isolation. This research paper aims to decipher the influence of key economic drivers on the economy, using the UK context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Duncheva et al (2020, p. 3) define the MMC as all the approaches that aim to optimise the construction process to obtain better products in less time. This could include offsite construction, lean construction, building information modelling (BIM) and simulation.…”
Section: Use Of the Modern Methods Of Construction And Production Pro...mentioning
confidence: 99%
“…Duncheva et al (2020, p. 3) define the MMC as all the approaches that aim to optimise the construction process to obtain better products in less time. This could include offsite construction, lean construction, building information modelling (BIM) and simulation.…”
Section: Use Of the Modern Methods Of Construction And Production Pro...mentioning
confidence: 99%
“…Minunno et al [13], for example, have shown how prefabrication in terms of reduction, reusability, adaptability, and recyclability of building components, provide environmental advantages. Further, Duncheva and Hairstans [15] describe the reduced need for onsite labour and inherent efficiency gains with the use of prefabrication as corresponding with the sustainability factor in circular economy. Despite these clear alignments, Osobajo et al [16] suggest that further research investigations are required to demonstrate circularity on prefabrication to support resource use and waste reduction objectives.…”
Section: Introductionmentioning
confidence: 99%